Folhas de atividades para o ensino de função afim e quadrática : conceito e aplicações - Silva, Roberta Angela da (2014)
After a careful evaluatation of my students, my principal investigator and I decided that students with difficulties in higher learning will be chosen, in this case, the first year of High School students in the three cities Jaboticabal, Monte Alto and Pontal. The math content to be worked upon was chosen from the assessment of difficulty students had learning first and second degree functions, as well as the importance the subject has when applied to other disciplines, such as Physics. To facilitate learning of these subjects, four activity sheets were composed to help improve text comprehension and reasoning, and consequently subject knowledge in such a way that the student builds the foundation concepts as to derive the affine and quadratic functions. Interactive exercises of multiple difficulties were prepared to inspire curiosity between students when solving problems. The exercises were designed to allow the students as much autonomy to finding solutions. The students were expected to develop: regularity identification, table-algebraic-graphic conversions, develop a problem situation without a previous explanation; relationship with the concept of affine function, justifying its proportionality; relationship with the concept of quadratic function; graphic analysis of quadratic functions; maximums and minimums; problems treatments on numeric fields and assay for algebraic fields; enthusiasm developing the activities; participation on activities discussion; the ability developing a problem situation with connection to different contexts; that the student had as much autonomy as possible on exercises solution; that the students build strategies and knowledge, given structure and organization to their thoughts, reaching a higher level of abstraction. Students were organized into pairs and encouraged to discuss while working on the activity sheet and review with each other in other classes the methods employed to solve the problems before the solutions were provided.